Pengaruh Macam Mulsa terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah - Adwityam Padma Putra Listariyanto; Achmad Fatchul Aziez; Tyas Soemarah Kurnia Dewi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
This study aims to determine the type of mulch that is effective for suppressing weed growth and the effect of using mulch on the growth of shallots (Allium ascalonicum L.). The research was carried out from September 2021 to December 2021 in the village of Central Jlko, Plosorejo, Matesih, Karanganyar Regency with an altitude of 380 meters above sea level and soil of the brown Litosol type. This research method used a Completely Randomized Block Design (RAKL) method consisting of one factor (single factor) and repeated 6 times with the following levels: A1: Without mulch, A2: Use of straw mulch, A3: Use of silver black plastic mulch, and A4: Use of husk mulch. The research results were analyzed using ANOVA or 5% variance. If it is significantly different, then continue with the Duncan's Multiple Range Test (DMRT) which shows that the type of mulch has a significant effect on shallot yields and has no significant effect on shallot growth. Silver black plastic mulch treatment (A3) was better than treatment without mulch (A1), straw mulch (A2), and rice husk mulch (A4) in inhibiting weed growth.